Displacement in the constructional/imperative styles in the collection (When the Quail Cries) (a stylistic study (Journal of the College of Basic Education, 2024)
The research dealt with the constructional/request methods, as these methods are the poet's material and stylistic feature in forming his various meanings, so their use varies within the poetic context in which they appear, so they go beyond their conventional meanings, to metaphorical meanings and connotations, to show the poet's ability from his language, as he hardly adheres to the conventional laws and norms in forming speech, as he is rebellious by nature, trying to reshape reality through his poetic text, so he benefits from what such methods produce and what he can form through them of connotations, so the research tried to monitor them within the semantic structure and monitor everything related to these methods included in the poet Khaled Al-Dahi's collection, through analysis once, and benefiting from statistical tables another time to reach objective results. As for the most important results that came out in this research, the semantic diversity produced by the use of these methods, within the poet's experience, came in multiples with the multiplicity of the context, and the most common method is the interrogative method that refers to the denial question and the confusion and dispersion that he lives.